Comparison of the Compositions of the Stool Microbiotas of Infants Fed Goat Milk Formula, Cow Milk-Based Formula, or Breast Milk - Gerald W. Tannock; Blair Lawley; Karen Munro; Shao J. Zhou; Maria Makrides; Robert A. Gibson; Thomas Sullivan; Colin G. Prosser; Dianne Lowry; Alison J. Hodgkinsong; Siva Gowri a/p Pathmanathan (American Society for Microbiology, 2024)
Indexed by Scopus